Providing Access to Educational TV for Children Using RFID Technology - Zapata, Mireya (2022)
Television is a communication medium found in most homes, facilitating accessibility to educational content through the reading-learning process. This paper presents a control system for educational television that allows the selection and playback of pre-recorded videos in a television decoder using RFID tags. This has been designed based on a controller that allows replacing the commands sent by a conventional remote control. To meet this educational objective, a prototype is developed from the mechanical, electronic and computer concept, to integrate a technological proposal that facilitates reading-learning, through a televised program and satellite transmission, integrating an instrument of personalized pedagogical assistance to an Ecuadorian spectacled bear for the assistance of children of a young age or with any type of disability that prevents them from handling a remote control. As a result, we obtained the experimental development of a basic prototype for learning-reading that works with connection to satellite equipment and activates the components for learning through television by means of an RFDI system. A unique tag is used for each pre-recorded program. When the RFID reader reads a tag that has been previously assigned, the TV module will transmit the sequence of signals needed to the TV decoder to play the specific movie or report.